PERSEPSI BUDAYA ORGANISASI DAN KOMITMEN TERHADAP KEPUASAN KERJA KARYAWAN BANK - Musran Munizu (Jurnal Keuangan dan Perbankan, 2010)
The purpose of this research was to analyze the ef fect among variables of organizational behavior, commitment , and employee sat isfact ion at PT. Bank SulSel Makassar. Thepopulat ion included all employee were 244 persons. There were 122 respondents part icipation in the survey. The respondents were chosen by simple random sampling technique f rompopulat ion. The data used consisted of primary data and secondary data collected by observation, interview, quest ionnaire, and documentat ion technique. Data was analyzed usingboth descript ive analysis, and St ructural Equat ion Modelling (SEM) performed by SPSS forwindows and AMOS 4.01. The results indicated following: (1) organizat ional behavior hadposit ive ef fect and signif icant to employee commitment ; (2) organizat ional behavior hadposit ive ef fect and signif icant to employee sat isfact ion; and (3) employee commitment hadposit ive ef fect and signif icant to employee sat isfact ion.